Glucose-Assisted Synthesis of Highly Dispersed LiMnPO4 Nanoparticles at a Low Temperature for Lithium Ion Batteries. (20th January 2016) - Xie, Zhengzheng; Chang, Kun; Li, Bao; Tang, Hongwei; Fu, Xiaoning; Chang, Zhaorong; Yuan, Xiao-Zi; Wang, Haijiang
Graphical abstract: Highlights: Full-dimensional nano-sized LiMnPO4 was synthesized in liquid-phase at a low temperature. The proposed LiMnPO4 have not only the uniform dispersion but also the good crystallinity. H-NMR spectrum confirmed that the generated APG could inhibit the growth of nanoparticles. Highly dispersed LiMnPO4 nanoparticles are beneficial for the uniform carbon coating. Abstract: The cathode material of the LiMnPO4 /C composite for lithium-ion batteries is successfully synthesized via a one-step glucose-assisted liquid-phase method in ethylene glycol (EG). The crystalline structure, morphology, micro-structure and particle size are characterized by X-ray diffraction (XRD), scanning electron microscope (SEM) and transmission electron microscope (TEM). XRD results show that the pure phase of LiMnPO4 with high crystallinity can directly be prepared in the liquid-phase assisted by glucose. SEM measurements confirm the uniform-sized nanorods of the LiMnPO4 morphology with a width of 20–50 nm and a length of 50–80 nm. TEM characterization reveals that the surface of the obtained LiMnPO4 nanorods is coated with a homogeneous carbon layer after a short heat treatment at a high temperature in the presence of glucose. This can be explained by the fact that the glycol glucoside generated during the refluxing of EG with glucose can effectively inhibit the growth and agglomeration of particles. Results of electrochemical tests show that the prepared LiMnPO4 /C nanorods exhibit not only a high initial discharge capacity of 155.3 mAh g −1 but also a good cycling stability, which retains 94% of the initial capacity over 100 cycles at 0.05 C.